Fluxos de Dióxido de Carbono na Interface Solo-atmosfera na Floresta Nacional do Tapajós - O ano de 2005 - Júnior, Miércio; Neto, Furtado; Figueira, Antonio P.; Barreto, Wilderclay M.; Tapajós, Raphael; Aguiar, Diego R.; Silva, Hudson; Silva, Rodrigo (Ciência e Natura, 2009)
.